ANALYSIS OF THE GINGIVAL RECESSION PREVALENCE AMONG DENTAL PATIENTS CONSIDERING ASSOCIATED AGE-RELATED, IATROGENIC AND PATHOLOGICAL CHANGES OF DENTAL STATUS - O.A. Krasnokutskyy; P.A. Hasiuk; M.Y. Goncharuk-Khomyn (Український стоматологічний альманах)
Assessment of gingival recessions prevalence and explicitation of their distribution among studied samples of dental patients considering criteria of age, sex, severity of gingival apical migration and the facts of associated dental status changes can potentially help to identify specific risk groups. Implementation of preventive measure among such risk groups could potentially optimize the prognosis of future conservative or surgical treatment of gingival recessions.